Paradox of public administration in India: Emerging issues - Rao, V. Bhaskara (1994)
"The author focuses on Indian Public Administration's difficulty in quickly matching constitutional ideals with operational goals of new government policies, "without tearing the socio-economic fabric," which is lessening its significance. He briefly suggests several remedial measures and underscores the urgency of their implementation"
Keywords: Public administration - India; Public administration